Racismo e psicanálise: a voz da mulher negra na literatura - Almeida, Natália de Sousa (2021)
This research aims to investigate, through a psychoanalytic analysis, the voices of black women resonating in the literary works The Color Purple by Alice Walker and Quarto de Despejo [Eviction room] by Carolina Maria de Jesus. For this, we made a historical, political and social rescue about racism, highlighting the racial issue as intensifier of the suffering of black women. Thus, we used strands of feminism that appropriate a decolonial politics to develop discussions about the double condition of oppression in being a woman and black. We brought some questions that locate psychoanalysis as a guide for the discussions of race. We used the studies of the Martiniquian psychoanalyst Frantz Fanon and the Brazilian psychoanalyst Neusa Sousa Santos to collaborate in the understanding of what it is like to be a black person. Based on these studies, we made a comparative analysis between the two literary works, focusing on the similarities between Alice Walker's and Carolina Maria de Jesus' writings about the condition of black women.